DIVERSIFIKASI SEBAGAI STRATEGI KEBERLANJUTAN PROGRAM KEWIRAUSAHAAN BERBASIS DIGITAL - Rahmad Solling Hamid; Suhardi M. Anwar; Imran Ukkas; Goso Goso (Universitas Ahmad Dahlan, 2023)
Diversification is a way to support the sustainability of digital-based strategies. The purpose of this research is to formulate a digital-based entrepreneurship development strategy. This study uses a qualitative approach through an interpretive paradigm. The population in this study was all young entrepreneurs between the ages of 25 and 40 years, and the sampling technique was non-probability sampling with a sample size of 280 respondents. A validity and reliability test was carried out for the data quality test with the result that all data was valid dan reliable. The analytical method used to formulate a digital-based marketing strategy was SWOT analysis (Strength, Weakness, Opportunity, Threat) by identifying the External Factor Analysis Strategy (EFAS) and the Internal Factor Analysis Strategy (IFAS). The result of this study shows that strategy formulation that should be obtained is using the opportunity to minimize weakness. Thus the rationalization strategy is the recommended strategy.